Pendidikan sebagai disiplin ilmu - Karimah, Fathiyatul (Maliki Interdisciplinary Journal, 2025)
Education as a scientific discipline is a conscious, planned effort designed to create a structured learning process to develop the potential of students as a whole. This study discusses the meaning, requirements, principles, benefits, and factors that make pencision a scientific discipline. In addition, this article also examines strategies for building learning communities in an educational context. By fulfilling requirements such as objectivity, systematicity and dynamics, education is able to become the main instrument in forming individuals who are critical, creative and have character. Principles such as learner-centered learning, collaboration, and a holistic approach emphasize the role of education as an interdisciplinary scientific discipline. Through innovation in learning methods and the integration of theory with practice, education can improve the quality of life and create a generation that is ready to face global challenges. nerasi yang siap menghadapi tantangan global.